2014
DOI: 10.1007/s00253-014-5975-1
|View full text |Cite
|
Sign up to set email alerts
|

Engineering color variants of green fluorescent protein (GFP) for thermostability, pH-sensitivity, and improved folding kinetics

Abstract: A number of studies have been conducted to improve chromophore maturation, folding kinetics, thermostability, and other traits of green fluorescent protein (GFP). However, no specific work aimed at improving the thermostability of the yellow fluorescent protein (YFP) and of the pH-sensitive, yet thermostable color variants of GFP has so far been done. The protein variants reported in this study were improved through rational multiple site-directed mutagenesis of GFP (ASV) by introducing up to ten point mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 33 publications
1
37
0
1
Order By: Relevance
“…It might be possible that once fast-folding FPs are folded, they become stable in the folded state and are resistant to unfolding by the mitochondrial protein import machinery. Indeed, it has been reported that GFP39N (F99S/M153T/V163A) displays higher thermostability than wild-type aqGFP (Aliye et al, 2015). Another possibility is that folded FPs prevent the binding of FFPs to mitochondrial-targeting factors or chaperones in the cytosol, which guide them to the mitochondrial surface.…”
Section: Discussionmentioning
confidence: 99%
“…It might be possible that once fast-folding FPs are folded, they become stable in the folded state and are resistant to unfolding by the mitochondrial protein import machinery. Indeed, it has been reported that GFP39N (F99S/M153T/V163A) displays higher thermostability than wild-type aqGFP (Aliye et al, 2015). Another possibility is that folded FPs prevent the binding of FFPs to mitochondrial-targeting factors or chaperones in the cytosol, which guide them to the mitochondrial surface.…”
Section: Discussionmentioning
confidence: 99%
“…However, some recent studies reported the development of more thermostable derivatives of GFP and also LOV‐based fluorescent proteins. For example, Aliye and coworkers developed a fast folding and thermostable YFP (FFTS‐YFP) that is stable at 75°C in vitro . Kiss et al .…”
Section: Discussionmentioning
confidence: 99%
“…To manipulate proteins more efficiently, rational design was invented. Rational design involves creating new molecules with certain functionalities by predicting how the molecule's structure will affect its behavior through physical models [12]. Although generally considered fast and accurate in modifying proteins, rational design can be more painstaking than directed evolution.…”
Section: Introductionmentioning
confidence: 99%